Measurable residual disease status and outcome of transplant in acute myeloid leukemia in second complete remission: a study by the acute leukemia working party of the EBMT - Gilleece, Maria H; Shimoni, Avichai; Labopin, Myriam; Robinson, Stephen; Beelen, Dietrich; Socié, Gerard; Unal, Ali; Ganser, Arnold; Vitek, Antonin; Sengeloev, Henrik; Yakoub-Agha, Ibrahim; Tholouli, Eleni; et al. (Blood cancer journal, 2021)
Measurable residual disease (MRD) prior to hematopoietic cell transplant (HCT) for acute myeloid leukemia (AML) in first complete morphological remission (CR1) is an independent predictor of outcome, but few studies address CR2. This analysis by the Acute Leukemia Working Party of the European Society for Blood and Marrow Transplantation registry assessed HCT outcomes by declared MRD status in a cohort of 1042 adult patients with AML CR2 at HCT. Patients were transplanted 2006-2016 from human leukocyte antigen (HLA) matched siblings (n = 719) or HLA 10/10 matched unrelated donors (n = 293). Conditioning was myeloablative (n = 610) or reduced-intensity (n = 432) and 566 patients (54%) had in-vivo T cell depletion. At HCT, 749 patients (72%) were MRD negative (MRD NEG) and 293 (28%) were MRD positive (MRD POS). Time from diagnosis to HCT was longer in MRD NEG than MRD POS patients (18 vs. 16 months (P < 0.001). Two-year relapse rates were 24% (95% CI, 21-28) and 40% (95% CI, 34-46) in MRD NEG and MRD POS groups (P < 0.001), respectively. Leukemia-free survival (LFS) was 57% (53-61) and 46% (40-52%), respectively (P = 0.001), but there was no difference in terms of overall survival. Prognostic factors for relapse and LFS were MRD NEG status, good risk cytogenetics, and longer time from diagnosis to HCT. In-vivo T cell depletion predicted relapse.
Keywords: Prognosis; senioři; lidé středního věku; Leukemia, Myeloid, Acute; Treatment Outcome; proporcionální rizikové modely; Female; mladý dospělý; výsledek terapie; Humans; dospělí; Aged; transplantace hematopoetických kmenových buněk; Male; ženské pohlaví; Hematopoietic Stem Cell Transplantation; Middle Aged; Young Adult; prognóza; lidé; indukce remise; reziduální nádor; mužské pohlaví; Adult; Remission Induction; Neoplasm, Residual; akutní myeloidní leukemie; Proportional Hazards Models